PENGEMBANGAN MODUL MATEMATIKA BERBASIS PENDEKATAN KONTEKSTUAL UNTUK PESERTA DIDIK KELAS XI SMA/MA - Wella Afriona (Departemen Matematika, 2021)
Abstract – This research aims to produce teaching materials in the form of a modules bassed on a contextual approach that is valid and practical. This research refers to in this study is the plomp model which consists of three stage. They are the preliminary research, prototype-ing stage and assessment phase. The preliminary research was data collection for designing modules. The stage of prototyping aims to develop modules in order to produce the modules valid and practical through the stages formative evaluation. The formative evaluations are self evaluation, expert review, on to one evaluaotion, and small grup. The instruments used in this development are student questionnaire, interview guide, observation sheet, checklist, validation sheet, and practicality sheet. The instrument, before use must be validated by the validator. This result of analysis of the data form the modules based on contextual approach developed are valid in terms of aspects of content eligibility, aspect of the language, aspects of the presentation, and aspects of the graphic with validation value is 89,79%. The modules based on contextual approach that is developed have also been practical in terms of aspect of ease of use, aspect of attractiveness, and aspect of the benefit with practical value is 90,897% from students and 95,56% from teacher. The dependent on these outcomes it very well may be presumed that modules can be utilized in the mathemaetic learning at the class. Keywords – Modules, Contextual approach, linear programming